Fabrication of β-Ga2O3/ZnO heterojunction for solar-blind deep ultraviolet photodetection. (30th January 2017) - Guo, D Y; Shi, H Z; Qian, Y P; Lv, M; Li, P G; Su, Y L; Liu, Q; Chen, K; Wang, S L; Cui, C; Li, C R; Tang, W H
Abstract: A thin-film type β -Ga2 O3 /ZnO heterojunction was constructed for the first time by radio frequency magnetron sputtering of a β -Ga2 O3 layer on a (0001) ZnO single crystalline substrate. The heterojunction presents a typical positive rectification in the dark, and shows a solar-blind deep ultraviolet photoelectric characteristic. Under zero bias, the photodetector based on a β -Ga2 O3 /ZnO heterojunction exhibits an I photo / I dark ratio of ∼14.8 under a 254 nm light illumination with a light intensity of 50 μ W cm −2, showing a characteristic of working with zero power consumption. The photocurrent linear increases and the response time decreases with the increase of the light intensity. The photodetector shows a R λ of 0.35 A W −1 and an EQE of 1.7 × 10 2 % under 254 nm illumination of 50 μ W cm −2 and a negative bias of 5 V. This study presents a promising candidate for use in solar-blind deep ultraviolet photodetection.